Fluidisation velocities during processing of whole soybean snack - Torrez Irigoyen, Ricardo Martin (2011)
Soybeans contribute to healthy nutrition because of the high proportion and quality of proteins. Its oil content is considerably lower than in peanuts, restricting energy intake. Precooked samples prepared at increasing drying–toasting times (lower moisture contents) experienced shrinkage and deformation. With the aim of determining design parameters for this process, fluid-dynamic studies of samples extracted at several times during drying–toasting allowed us to determine laminar and turbulent coefficients of the Ergun equation and the minimum fluidisation velocity (Vmf), at ambient temperatures. The turbulent coefficient increased for decreasing moistures and Vmf varied from 2.6 and 1.2 m/s over a 60 min process. As drying–toasting must be conducted at 140 °C, an increase by 20% in Vmf is required. Operating velocities were 50% above Vmf to produce uniform treatment. As the system requires a decreasing fluidisation velocity with time, an automatic control with time-varying target value should be devised to limit energy consumption and prevent solid losses.